Utilization of fruit peels as carbon source for white rot fungi biomass production under submerged state bioconversion - Saheed, Olorunnisola Kola; Jamal, Parveen; Abdulkarim, Mohd Ismail; Alam, Md Zahangir; Muyibi, Suleyman Aremu (Elsevier, 2016)
The present generation of nutrient rich waste streams within the food and hospitality industry is inevitable and remained a matter of concern to stakeholders. Three white rot fungal strains were cultivated under submerged state bioconversion (SmB). Fermentable sugar conversion efficiency, biomass production and substrate utilization constant were indicators used to measure the success of the process. The substrates – banana peel (Bp), pineapple peel (PAp) and papaya peel (Pp) were prepared in wet and dried forms as substrates. Phanerochaete chrysosporium (P. chrysosporium), Panus tigrinus M609RQY, and RO209RQY were cultivated on sole fruit wastes and their composites. All fungal strains produced profound biomass on dry sole wet substrates, but wet composite substrates gave improved results. P. tigrinus RO209RQY was the most efficient in sugar conversion (99.6%) on sole substrates while P. tigrinus M609RQY was efficient on composite substrates. Elevated substrate utilization constant (Ku) and biomass production heralded wet composite substrates. P. chrysosporium was the most performing fungal strain for biomass production, while PApBp was the best composite substrate.